Efektivitas Model Pembelajaran Word Square Terhadap Hasil Belajar IPS Siswa Kelas III Madrasah Ibtidaiyah Ma’had Al-Zaytun - Mayka Aulia Rahma Wahyuningsih; Dewi Utami; Iis Humaeroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effectiveness of the Word Square learning model on the learning outcomes of social studies of grade III students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. This study applies a quantitative method with the type of One-Group Pretest-Posttest research. Data collection is in the form of tests, questionnaires and documentation. To determine the effectiveness of the Word Square learning model on social studies learning outcomes, a hypothesis test in the form of a Paired Sample T-Test and an N-Gain Score test was used. The sample in this study was taken using the Non Probability Sampling technique, namely one class III B01 with 20 students. The results of the study indicate that the Word Square learning model is effective on the learning outcomes of social studies of grade III students of Madrasah Ibtidaiyah Ma'had Al-Zaytun, with the results of the Paired Sample T-Test sig 2 tailed value of 0.000 <0.05. Then the effectiveness of the Word Square learning model on the learning outcomes of social studies students of class III of Madrasah Ibtidaiyah Ma'had Al-Zaytun was proven through the results of the N-Gain Score test with a High criterion of 0.72 and the acquisition of questionnaire data with interpretation criteria that were classified as Strong at 61%.